Strategi Edukasi Publik tentang Fungsi dan Layanan Ombudsman: Inovasi Edukasi dan Diseminasi untuk Masyarakat Luas - Putera, Roni Ekha; Valentina, Tengku Rika; Purnama, Tirza Haqia; Firdaus (Sawala : Jurnal Administrasi Negara, 2024)
The Ombudsman plays a crucial role in overseeing the provision of public services. However, awareness and understanding of the Ombudsman’s functions and services remain low, particularly among rural communities and those with lower levels of education. This study aims to explore effective public education strategies to enhance public understanding of the Ombudsman. The research adopts a qualitative and descriptive approach, supported by related literature reviews. The theory used in this study is Kotten’s strategy theory as cited in Salusu (2008). The three indicators utilized in this research are organizational strategy, resource support strategy, and program strategy. The findings indicate that while the Ombudsman’s strategies are generally good, they have not yet succeeded in reaching all segments of society. Therefore, the authors offer several recommendations, including approaches that involve local communities and the use of easily accessible media to enhance the effectiveness of education efforts. Programs such as Ombudsman ambassadors, Ombudsman representatives at the district level, and competitions or festivals focused on the functions and services of the Ombudsman are suggested as solutions to attract public attention and participation. Additionally, partnerships with schools and community organizations have shown positive impacts in broadening the reach of information. It is hoped that awareness and understanding of the Ombudsman will increase, enabling the public to be more proactive in utilising the services provided by the Ombudsman